2018
DOI: 10.4038/sljas.v23i1.7552
|View full text |Cite
|
Sign up to set email alerts
|

Microbial and chemical quality of selected dried fish varieties available in Sri Lankan market

Abstract: Dried fish is one of the traditionally preserved foods in Sri Lanka.Since dried fish is often an important component of daily meal, this study was aimed to assess the quality of selected dried fish varieties in the local market. Dried fish samples of nine selected varieties were collected under three categories, viz. locally produced, imported dried fish before and after distribution to retail market. They were analyzed for microbiological and chemical parameters. Water activity of the samples was also measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The A w values in this study were lower than 0.8 described by Koral et al (2013), and 0.77 reported by Lin et al (2012); irrespective of the season of sampling, however, they were higher than 0.5 reported by Geetha et al (2014). Salt and drying processes are key factors contributing significantly to reduction of TVCs, MCs, and A w in products (Ginigaddarage et al, 2018;Majumdar et al, 2017). The MCs and A w values reported in the different salted sun-dried Nile perch products can be expected to support microbial growth during the rainy season so that products undergo microbial spoilage faster than those processed in the dry season.…”
Section: Resultsmentioning
confidence: 99%
“…The A w values in this study were lower than 0.8 described by Koral et al (2013), and 0.77 reported by Lin et al (2012); irrespective of the season of sampling, however, they were higher than 0.5 reported by Geetha et al (2014). Salt and drying processes are key factors contributing significantly to reduction of TVCs, MCs, and A w in products (Ginigaddarage et al, 2018;Majumdar et al, 2017). The MCs and A w values reported in the different salted sun-dried Nile perch products can be expected to support microbial growth during the rainy season so that products undergo microbial spoilage faster than those processed in the dry season.…”
Section: Resultsmentioning
confidence: 99%
“…Another study conducted in Sri Lanka has shown that 91% of the imported dried fish samples and 54% of locally manufactured dried fish samples contained salt content above 12%. Further it showed, local samples had less amount of salt compared to imported samples (Ginigaddarage et al, 2018).…”
Section: Salt Contentmentioning
confidence: 95%
“…However, occurrence of Aspergillus and Penicillium were reported in dry fish from India (Prakash et al., 2011). In a separate study, the dry fish were reported to be free of pathogenic bacteria S. aureus , E. coli , and halophilic bacteria (Ginigaddarage et al., 2018). The above results suggest the need to adhere to good practices during sun drying.…”
Section: Effects Of Preservation and Processing On Microbiological Sa...mentioning
confidence: 99%